2012
DOI: 10.1007/s00432-012-1269-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphisms in IL-12A, IL-12B, IL-12Rβ1, IL-27 gene and serum levels of IL-12p40, IL-27p28 with esophageal cancer

Abstract: Our data suggest that the impaired production of IL-12p40 and IL-27p28 behaves as risk factors for esophageal cancer occurrence. IL-12B gene rs3212227 CC/AC and IL-12Rβ1 gene 378 GG/GC genotypes, which associated with decreased IL-12p40 level, may contribute to esophageal cancer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…[14][15][16] Primer sequences used in the present study are shown in Table 1 (Bio Basic, Ontario, Canada). [14][15][16] Each PCR reaction mix comprised 55 ng genomic DNA, 200 mM dNTP, 1U Taq DNA polymerase (Fermentas AB, Vilnius, Lithuania) and 100 mM primers, in a total volume of 25 ml. The cycling programme involved preliminary denaturation at 95 C for 5 min, followed by 32 cycles of denaturation at 94 C for 45 s, annealing at 60 C for 45 s, and elongation at 72 C for 45 s, followed by a final elongation step at 72 C for 7 min.…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%
“…[14][15][16] Primer sequences used in the present study are shown in Table 1 (Bio Basic, Ontario, Canada). [14][15][16] Each PCR reaction mix comprised 55 ng genomic DNA, 200 mM dNTP, 1U Taq DNA polymerase (Fermentas AB, Vilnius, Lithuania) and 100 mM primers, in a total volume of 25 ml. The cycling programme involved preliminary denaturation at 95 C for 5 min, followed by 32 cycles of denaturation at 94 C for 45 s, annealing at 60 C for 45 s, and elongation at 72 C for 45 s, followed by a final elongation step at 72 C for 7 min.…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%
“…The -964A/G polymorphism (rs153109) of IL-27p28 gene promoter was first identified in a case-control study and showed a relationship with asthma susceptibility (6). After that, several case-control studies were conducted to investigate the association between IL-27p28 gene -964A/ G polymorphism and cancer risk in Chinese population (7)(8)(9)(10)(11)(12)(13)(14). However, conflicting results were observed, which might be caused by small sample size of each individual study.…”
Section: Introductionmentioning
confidence: 99%
“…It was only shown that the IL12B rs3212227 SNV affected the circulating levels of IL-12 p40. 29,30 Among other immune response abnormalities in uremic patients, the secretion of IL-12 was reported to be disturbed. In vitro studies showed that dendritic cells of HD patients secrete more IL-12 p70, the active form of IL-12 (after incubation both in uremic serum and serum of healthy individuals), and that the functioning of these cells is significantly impaired.…”
mentioning
confidence: 99%